Abu Umair, Fayez Abdul Fattah. “Guidelines for Textual Criticism according to the Qur’an and Sunnah,” Year 10, Issue 39 (Winter 1426 AH/ 2005 CE), Pp. 147-188. - أبو عمير, فايز عبد الفتاح (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2005)
Fayez Abu Umair’s article begins with a preface on the guarantees and self- regulations that ensure the preservation and continuation of religion. It then discusses the meaning of naqd (criticism) in terminology and usage, and the strong correlation between the meanings and what is understood of procedural processes carried out in critiquing the text to ensure correct critique without any venturing. The article goes on to distinguish between the sciences of riwāyah (narration) and dirāyah (understanding of hadith), and discusses the reasons for textual criticism (wrong/ ill intention, illusion, forgetfulness, error, differences in understanding and partial readings). In sum, the article examines the rules of criticism according to the Qur’an and Sunnah, and it concludes with an illustration of the methodology utilized in textual criticism.